ANALISIS OBSERVASI HASIL BELAJAR SISWA SD KELAS III DAN KELAS V PADA MATA PELAJARAN MATEMATIKA DI KOTA MEDAN, KABUPATEN DELI SERDANG DAN KABUPATEN LANGKAT - Titin Rahmayanti Rambe; Fasti Rola; Sumarlin Mangandar Marianus; Anggili Pratama; Jhonas Dongoran; Hasratuddin Hasratuddin (Universitas Negeri Medan, 2023)
This study uses a qualitative descriptive method that aims to understand the phenomena of elementary mathematics learning outcomes. The resulting data is presented in the form of numbers described in the description. Research using the observation method was conducted on mathematics learning outcomes in grades III and grade V of elementary schools spread across three districts/cities in North Sumatra Province. To understand students' errors and misconceptions is essential for the effective teaching and learning of mathematics. It is important for teachers to approach student mistakes in a constructive way, helping students understand their mistakes and learn from them. Research has been conducted to investigate patterns of student misunderstandings, errors, and misunderstandings across educational systems, grade levels, gender, and time. Several case studies of mathematics subjects in elementary schools in North Sumatra Province became the main focus of the North Sumatra Education Office so that they held improvement and development activities for Chemistry, Biology, Physics and Mathematics subjects in 2022. The conclusion showed that only three grades III fulfilled and 1 class V that meets above the value of 70.